Experimental Investigation and Numerical Determination of Custom Gas Diffusion Layers on PEMFC Performance - S. Shimpalee (2018)
© 2016 Elsevier Ltd The objective of this work is to investigate the design of gas diffusion layer (GDL) for fuel cells that possess specific transport properties. Various types of custom GDLs that have a microporous bilayer (MP) were studied. These GDLs have two different MP layers and a carbon substrate. GDLs with different bilayer MPs designs were tested and the fuel cells performance was investigated. The performance of the fuel cell was measured in-situ with different GDLs at several operating conditions. The pore morphology of the GDLs as well as pore size distribution of the GDLs including the MPs was determined. The data on the pore size distribution including the relationship between tortuosity and porosity was used as model parameters. The experimental data and model predictions confirm that introducing the bilayer MPs on the substrate could improve the transport resistant and increase the performance of PEMFC. The effect of carbon particle size and overall diffusivity also modified the value of MacMullin number and overall thickness of GDL causing the differences in performance and local distributions.